Mechanistic insights into adipose-derived stem cells and exosomes in ischemia-reperfusion injury repair: from shared pathways to organ-specific therapeutics - Jiaqian Si; Jie Wang; Hao Dai; Tuochen Lv; Songyun Zhao; Wanying Chen; Liqun Li; Siqi Ding; Yucang He (Frontiers in Cell and Developmental Biology)
Ischemia-reperfusion injury (IRI) has become a significant challenge for clinical treatment due to the complex multi-mechanism pathological cascade response, including oxidative stress, inflammatory bursts, and programmed cell death. Adipose-derived stem cells (ADSCs) and their exosomes (ADSCs-exosomes) are emerging as a breakthrough therapeutic strategy to reverse IRI, owing to their multi-target synergistic effects. This review systematically analyzes the two major repair modes of ADSCs and ADSCs-exosomes: the “common protection” mechanism, which includes anti-inflammatory, anti-oxidative, and anti-apoptotic effects through paracrine regulation of miRNAs targeting the NF-κB/NRF2/β-catenin signaling axis; and precision repair, which is achieved through organ-specific targets, including hepatic mitochondrial dynamics and pyroptosis inhibition, cardiac macrophage polarization and neutrophil clearance, renal anti-fibrosis and erythropoietin (EPO) activation, as well as brain iron death regulation and microglial remodeling. From the perspective of the mechanism interaction network, this paper first proposes a theoretical framework of “multi-organ shared core pathways and dynamic regulation of different targets.” It also reviews the translational potential of combined therapeutic strategies based on engineered exosomes delivery systems and biomaterials, emphasizing the optimization of delivery efficiency and functional enhancement to address the bottleneck of clinical applications. The ADSCs-mediated IRI intervention system provides an essential theoretical and technical basis for the development of individualized precision therapies.